The Impact of Pectin Supplementation on Intestinal Barrier Function in Healthy Young Adults and Healthy Elderly - Wilms, Ellen (Nutrients, 2019)
Intestinal barrier function is suggested to decrease with aging and may be improved by pectin intake. The aim of this study was to investigate the effects of four weeks pectin supplementation on gastrointestinal barrier function in vivo and ex vivo in different age groups. In a randomized, double-blind, placebo-controlled, parallel study, 52 healthy young adults (18–40 years) and 48 healthy elderly (65–75 years) received 15 g/day pectin or placebo for four weeks. Pre- and post-intervention, in vivo gastrointestinal permeability by a multisugar test, and defense capacity in mucosal samples were assessed. Sigmoid biopsies were collected post-intervention from subgroups for Ussing chamber experiments and gene transcription of barrier-related genes. Pectin intervention did not affect in vivo gastroduodenal, small intestinal, colonic, and whole gut permeability in young adults nor in elderly (p ≥ 0.130). Salivary and fecal sIgA and serum IgA were not significantly different between pectin versus placebo in both age groups (p ≥ 0.128). In both young adults and elderly, no differences in transepithelial electrical resistance and fluorescein flux (p ≥ 0.164) and relative expression of genes analyzed (p ≥ 0.222) were found between pectin versus placebo. In conclusion, intestinal barrier function was not affected by four weeks pectin supplementation neither in healthy young adults nor in healthy elderly.